Halophilic Aspergillus penicillioides from athalassohaline, thalassohaline, and polyhaline environments - Nazareth, Sarita W.; Gonsalves, Valerie (Frontiers in Microbiology, 2014)
Aspergillus penicillioides is a true halophile, present in diverse econiches – from the hypersaline athalassohaline and thalassohaline environments, to polyhaline systems, and in different geographical locations. Twenty seven isolates from these environments, were seen to be moderate halophiles, euryhaline in nature. They had an obligate need of a low aw and were unable to grow on a regular defined medium such as Czapek Dox Agar, as well as on varied nutrient rich agar media such as Malt Extract, Potato Dextrose and Sabouraud Agar; however, growth was obtained on all these media when amended with 10% solar salt. In absence of added salt, the conidia either did not germinate, or when germinated, distortions and lysis were seen in the short mycelial forms; on media with salt, the mycelia and vesicles appeared normal.